2020
DOI: 10.3390/instruments4040032
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Identification in Ocean Water Samples by Means of 50 keV Energy Electron Beam

Abstract: This study presents a new methodology to reveal traces of polyethylene (the most common microplastic particles, known as a structure of C2H4) in a sample of ocean water by the irradiation of a 50 keV, 1 µA electron beam. This is performed by analyzing the photon (produced by the electrons in water) fluxes and spectra (i.e., fluxes as a function of photon energy) with different types of contaminated water using an adequate device and in particular looking at the peculiar interactions of electrons/photons with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Given the current pandemic as a result of SaRSCoV-2, causing CoVID-19, and the possibility of more viruses crossing species boundaries resulting in yet more viral epidemics, the need for detection of these infectious agents is critical to controlling current and future outbreaks of infectious diseases caused by viruses. Here we have reported that the technology for detecting these infectious agents could exist and could result in quantifiable measurements of ambient viral particles [2].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Given the current pandemic as a result of SaRSCoV-2, causing CoVID-19, and the possibility of more viruses crossing species boundaries resulting in yet more viral epidemics, the need for detection of these infectious agents is critical to controlling current and future outbreaks of infectious diseases caused by viruses. Here we have reported that the technology for detecting these infectious agents could exist and could result in quantifiable measurements of ambient viral particles [2].…”
Section: Discussionmentioning
confidence: 99%
“…The nucleic acid found in viruses can consist of either RNA or DNA. The Coronaviridae, for example contain a single molecule of RNA consisting of about 30 Kilobases in length where Kb stands for unit of measurement of DNA or RNA length used in genetics [1][2][3][4][5][6]. RNA is composed of nucleotides, each containing a sugar (deoxyribose), a nitrogen containing base (adenine, uracil, guanine, and cytosine), and a phosphate group PO 4 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations